Exam anxiety and its relationship to academic achievement among second-year secondary school students in Sabha city (Journal of Human Sciences, 2025)
The researcher, via this paper, aimed to determine the correlation between test anxiety and academic achievement among secondary school students in Sebha city. The researcher used the descriptive approach in her study and the research sample consisted of 60 male and female students. It is worth mentioning that the questionnaire was used for collecting information and it enjoyed acceptable validity and reliability. Finally, the most significant findings of this study were as follows: There are no statistically significant differences between males and females in the level of anxiety. There are statistically significant differences between males and females in the level of academic achievement in favour of females.